Cystatin C and risk of vascular and nonvascular mortality: a prospective cohort study of older men. - Emberson, JR; Haynes, R; Dasgupta, T; Mafham, M; Landray, M; Baigent, C; Clarke, R (2010)
OBJECTIVE: To assess the relevance of cystatin C, as a marker of mild-to-moderate renal impairment, for vascular and nonvascular mortality in older people. DESIGN: Prospective cohort study. SETTING: Re-survey in 1997 to 1998 of survivors in the 1970 Whitehall study of London civil servants. SUBJECTS: Five thousand three hundred and seventy-one men (mean age at resurvey: 77 years) who took part in the resurvey and had plasma cystatin C concentration measured. MAIN OUTCOME MEASURES: Cause-specific mortality over subsequent 11 years (1997 to 2008). METHODS: Cox regression was used to estimate the associations of cystatin C with vascular and nonvascular mortality, before and after adjustment for prior disease and other risk factors (including lifetime blood pressure). RESULTS: During an 11.0-year follow-up period, there were 1171 deaths from vascular causes [26 per 1000 per year (py)] and 1615 deaths from nonvascular causes (36 per 1000 py). Compared with men with cystatin C in the bottom fifth of the distribution, men in the top 10th had about two-fold higher mortality rates from vascular and nonvascular mortality (fully adjusted P both <0.001) even after adjustment for prior disease and all measured confounders, including lifetime blood pressure. The fully adjusted relative risks per 50% higher cystatin C concentrations were 1.66 [95% CI 1.48 to 1.85] for vascular mortality, 1.92 [95% CI 1.66 to 2.22] for ischaemic heart disease mortality and 1.46 [95% CI 1.31 to 1.61] for nonvascular mortality. CONCLUSIONS: In older men, plasma concentration of cystatin C, probably as a marker of mild renal disease, is a strong independent predictor of both vascular and nonvascular mortality.